Faktor-Faktor Yang Mempengaruhi Perubahan Anggaran Pemerintah Daerah - Yeni Fahrinda (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2022)
This article reviews several factors that influence rebudgeting in local government, these factors include remaining over budget calculations, local revenue, and balancing funds. This article aims as a hypothesis that builds the influence between variables so that it can be used in further research. Rebudgeting in local government is a common thing in a budget period, taking into account several supporting circumstances. This article shows that the remaining over budget calculations, local revenue and balancing funds have an effect in rebudgeting on local government.